Sex‐ and Age‐Related Differences in the Clinical and Neuroimaging Characteristics of Patients With Spontaneous Intracranial Hypotension: A Records Review. Issue 8 (9th July 2016) - Tanaka, Yukitaka; Tosaka, Masahiko; Fujimaki, Hiroya; Honda, Fumiaki; Yoshimoto, Yuhei
Abstract : Background: The significance of sex‐ and age‐related differences in the clinical course of spontaneous intracranial hypotension (SIH) was investigated. Methods: We retrospectively studied 40 consecutive patients (female:male = 28:12, median age 41.5 years) treated under clinical diagnoses of SIH satisfying the International Classification of Headache Disorders 3rd edition criteria, including 37 patients (92.5%) with diffuse pachymeningeal enhancement. The patients were divided into two groups by age and sex, and the clinical and neuroimaging findings in each group were investigated. Results: Acute onset (female:male = 82.1%:50.0%, P = .042), severe headache (75.0%:41.7%, P = .045) occurred with higher frequency in females than in males, and SDH occurred with lower frequency in females than in males (28.6%:75.0%, P = .006). Duration until the consultation (2:14 days, P = .022), SDH thickness (0:7.1 mm, P = .001), and iter displacement (1.6:7.1 mm, P = .004) was greater in males. Acute onset (Younger [≤40 years]: older [>40 years] = 94.1%:56.5%, P = .012), occurred with higher frequency in younger patients, and duration until the consultation (1:5 days, P = .001), frequency of SDH (17.7%:60.9%, P = .010), SDH thickness (0:5.9 mm, P = .003), in older patients. All nine patients with thunderclap headache were female, with median age of 37 years. Conclusions: More severe clinical symptoms with acute onset were observed in females and younger patients of SIH. Comparatively rare subdural hygroma/hematoma on magnetic resonance imaging might result from the shorter duration to diagnosis in females and younger patients. Key words : spontaneous intracranial hypotension, sex, age, magnetic resonance imaging, thunderclap headache